2013
DOI: 10.1089/met.2012.0109
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Metabolic Syndrome in Young Hispanic Women: Findings from the National Sister to Sister Campaign

Abstract: In a large, nationally representative sample of women, we found that metabolic syndrome was highly prevalent among young Hispanic women. Efforts specifically targeted to identifying these high-risk women are necessary to prevent the cardiovascular morbidity and mortality associated with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Patients with HCC are at risk for complications and mortality from cirrhosis, HCC, and other comorbidities. Consistent with prior studies, we found that Hispanic patients had higher rates of comorbidities including metabolic syndrome[19,20] and ESRD[21-23]. Our data builds on existing literature by showing that these differences persist in patients with HCC.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with HCC are at risk for complications and mortality from cirrhosis, HCC, and other comorbidities. Consistent with prior studies, we found that Hispanic patients had higher rates of comorbidities including metabolic syndrome[19,20] and ESRD[21-23]. Our data builds on existing literature by showing that these differences persist in patients with HCC.…”
Section: Discussionsupporting
confidence: 90%
“…MAP3K9 was most strongly associated among women with the highest IA ancestry and multiple SNPs in this gene interacted with a history of diabetes to alter risk of breast cancer. At a population level, rates of diabetes and metabolic syndrome are higher among Hispanic, Native American and Mexican women than among NHW women [4547]. While assessment of interaction of diet and lifestyle factors within ancestry groups would be desirable, our power was limited to meaningfully evaluate these 3-way interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Different populations have different risk to MA and MS. INTERHEART and INTERSTROKE studies demonstrated that abdominal obesity (AO) in Latin American countries was the highest cardiovascular risk factor compared with the rest of the world (Lanas et al, ; O'Donnell et al, ). Studies conducted in the United States show a higher prevalence of MA and MS in the general Latino population, with figures showing around a 50%‐60% higher risk of MS (Daviglus et al, ; Rodriguez, Naderi, Wang, Johnson, & Foody, ; Roger et al, ). Echoing these results, studies in psychotic patients show that Latino patients have a significantly higher prevalence of MS than non‐Latino ones (Kato, Currier, Gomez, Hall, & Gonzalez‐Blanco, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite different studies have shown that antipsychotic-naïve first-episode psychosis patients do not differ in their baseline rates of MS in comparison with healthy subjects (Fleischhacker et al, 2013;Mitchell, Vancampfort, Sweers, et al, 2013), they rapidly add more metabolic risk factors during the first year of treatment (Curtis et al, 2011 (AO) in Latin American countries was the highest cardiovascular risk factor compared with the rest of the world (Lanas et al, 2007;O'Donnell et al, 2010). Studies conducted in the United States show a higher prevalence of MA and MS in the general Latino population, with figures showing around a 50%-60% higher risk of MS (Daviglus et al, 2012;Rodriguez, Naderi, Wang, Johnson, & Foody, 2013;Roger et al, 2011). Echoing these results, studies in psychotic patients show that Latino patients have a significantly higher prevalence of MS than non-Latino ones (Kato, Currier, Gomez, Hall, & Gonzalez-Blanco, 2004).…”
Section: Introductionmentioning
confidence: 99%